Narcolepsy treatment: from exorcism and bloodletting to modern therapy with histamine receptor inverse agonists - Sakalauskaitė-Juodeikienė, E.; Masaitienė , R. (Neurologijos seminarai, 2020)
In this review article, we present the treatment of narcolepsy since ancient times when patients experiencing the phenomenon of incubus (today understood as sleep paralysis with hypnagogic or hypnopompic hallucinations) were “cured” during the sessions of exorcism. At the beginning of the 19th century, in Vilnius clinics, the incubus disease was treated by providing lifestyle, diet, and sleep hygiene recommendations, also using antiphlogistic methods, as well as antispasmodic medicine and quinine bark. It was not until the late 20th century, when narcolepsy was perceived as a central hypersomnia due to partial or complete loss of hypocretin-secreting neurons in the hypothalamus, that effective symptomatic treatment emerged. Psychostimulants such as modafinil, armodafinil, pitolisant, and sodium oxybate were the first-line strategies. In second line, methylphenidate could be used. Amphetamine mixed salts or D-amphetamine could only be used in the third line because of potential cardiovascular and psychiatric side effects. Sodium oxybate, pitolisant, and venlafaxine were the first-line medications recommended for cataplexy. Serotonin and noradrenaline reuptake inhibitors were also often prescribed to manage cataplexy, while low doses of tricyclic antidepressants were used as third-line treatment. In this paper, we also present new European management guidelines for narcolepsy presented in 17th European Narcolepsy Masterclass in Berlin in September 5, 2020. Pitolisant, one of the latest drugs used for the symptomatic treatment of type I and II narcolepsy in adults, is a unique histamine H3 receptor antagonist/reverse agonist, the only wake-promoting agent in the market without risk of abuse. Currently, the treatment of narcolepsy with pitolisant is reimbursed in Lithuania. In this article, we also review future perspectives for narcolepsy treatment including novel versions of sodium oxybate, the noradrenaline reuptake inhibitor reboxetine, the combination of modafinil and the astroglial connexins inhibitor flecainide, selective hypocretin-2 receptor agonists, and immune-based therapies.